The future of e-learning in healthcare professional education: some possible directions - Kieran Walsh (Istituto Superiore di Sanità, 2014)
E-learning in healthcare professional education still seems like it is a new innovation but the reality is that e-learning has been around for as long as the internet has been around. This is approximately twenty years and so it is probably appropriate to now take stock and consider what the future of e-learning in healthcare professional education might be. One likely occurrence is that there will be more formats, more interactive technology, and sometimes game-based learning. Another future of healthcare professional education will likely be in simulation. Like other forms of technology outside of medicine, the cost of e-learning in healthcare professional education will fall rapidly. E-learning will also become more adaptive in the future and so will deliver educational content based on learners' exact needs. The future of e-learning will also be mobile. Increasingly in the future e-learning will be blended with face to face education.